Effects of additional ablation of low‐voltage areas after Box isolation for persistent atrial fibrillation. Issue 2 (15th February 2019) - Kumagai, Koichiro; Toyama, Hideko; Zhang, Bo
Abstract: Background: Previous studies reported that ablation of low‐voltage areas (LVAs) after pulmonary vein isolation (PVI) improves the success rate in persistent atrial fibrillation (PerAF) patients with LVAs. However, the need for LVA ablation in addition to the posterior left atrial isolation, Box isolation (BOXI), for PerAF is unclear. We evaluated the effects of LVA ablation after BOXI for PerAF with LVAs. Methods: In 115 patients with PerAF (75 longstanding PerAF), LA voltage maps were created during sinus rhythm after PVI. Subsequently, BOXI was performed. In 61 patients without LVAs (<0.5 mV), BOXI alone was performed. Fifty‐four patients with LVAs were randomly assigned to BOXI plus LVA ablation (33 patients) or BOXI alone (21 patients). Results: The rate of AF termination or cardioversion after BOXI was significantly higher than that after PVI (100% vs 88%, P  < 0.001). The inducibility of atrial tachyarrhythmia after BOXI was significantly lower than that after PVI (27% vs 100%, P  < 0.001). During 24 ± 9 months of follow‐up after a single procedure, atrial tachyarrhythmia‐free rate in the patients with LVAs, was significantly lower than that without LVAs (65% vs 82%, P  = 0.043). However, the success rate was not significantly different between the BOXI plus LVA ablation group and the BOXI alone group of patients with LVAs (67% vs 62%, P  = 0.722). Conclusion: BOXI facilitates AF termination and its non‐inducibility. Among patients with PerAF, BOXI alone may be adequate in cases without LVAs. Although cases with LVAs have higher risk of AF recurrence, additional LVA ablation does not improve the outcomes much.